Innovation in management of dysmenorrhea: A nursing approach - Dini, Yunita Arga; Bukuku, Debora (Universitas Muhammadiyah Magelang, 2021)
Dysmenorrhea is abdominal pain caused by uterine cramps that occur during menstruation. The pain is caused by the onset of menstruation and lasts several hours to several days until it reaches the peak of pain. However, many people still do not know about the management of dysmenorrhea. This causes an increase in abdominal pain which often interferes with daily activities. Therefore, this review is structured to describe the various treatments for dysmenorrhea. The results of this review can be used as part of the education of patients who complain of dysmenorrhea and also as an innovation development in the field of reproductive health.